The Effectiveness of Google Form–Based Digital Attendance in Improving Student Discipline in Educational Settings - Dafa Akhdan Nasywa; Rizki Ahmad Syabani; Nurul Malikah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
The rapid development of digital technology has encouraged educational institutions to adopt technology-based innovations in learning administration, including attendance systems. One such innovation is the use of Google Forms as a digital attendance tool. This study aims to analyze the effectiveness of Google Form–based digital attendance in supporting student discipline and improving the efficiency of learning administration.This research employed a quantitative descriptive approach using a survey method. Data were collected through closed-ended questionnaires distributed to students who had experience using Google Form–based attendance during learning activities. The questionnaire measured students’ perceptions of ease of use, efficiency, accuracy, and the impact of digital attendance on their learning discipline. The collected data were analyzed using descriptive statistical techniques to identify response patterns and overall trends. The findings indicate that Google Form–based digital attendance is perceived as practical, efficient, and easy to use by most respondents. The system helps reduce administrative errors, minimizes paper usage, and encourages students to be more disciplined in attending classes. In addition, digital attendance facilitates better data management and monitoring of student participation in learning activities.In conclusion, Google Form–based digital attendance has significant potential as an effective and economical solution for learning administration in educational institutions. Its implementation not only supports administrative efficiency but also contributes to improving student discipline and promoting the integration of digital technology in education. Future research is recommended to explore the long-term impact of digital attendance systems on student behavior and learning outcomes using mixed or experimental research designs.